Effects of inoculation with active microorganisms derived from adult goats on growth performance, gut microbiota and serum metabolome in newborn lambs - Fu, Lin; Wang, Liaochuan; Liu, Li; Zhang, Li; Zhou, Ziyao; Zhou, Yan; Wang, Gaofu; Loor, Juan J.; Zhou, Peng; Dong, Xianwen (Frontiers in Microbiology, 2023)
This study evaluated the effects of inoculation with adult goat ruminal fluid on growth, health, gut microbiota and serum metabolism in lambs during the first 15 days of life. Twenty four Youzhou dark newborn lambs were selected and randomly distributed across 3 treatments (n = 8/group): autoclaved goat milk inoculated with 20 mL sterilized normal saline (CON), autoclaved goat milk inoculated with 20 mL fresh ruminal fluid (RF) and autoclaved goat milk inoculated with 20 mL autoclaved ruminal fluid (ARF). Results showed that RF inoculation was more effective at promoting recovery of body weight. Compared with CON, greater serum concentrations of ALP, CHOL, HDL and LAC in the RF group suggested a better health status in lambs. The relative abundance of Akkermansia and Escherichia-Shigella in gut was lower in the RF group, whereas the relative abundance of Rikenellaceae_RC9_gut_group tended to increase. Metabolomics analysis shown that RF stimulated the metabolism of bile acids, small peptides, fatty acids and Trimethylamine-N-Oxide, which were found the correlation relationship with gut microorganisms. Overall, our study demonstrated that ruminal fluid inoculation with active microorganisms had a beneficial impact on growth, health and overall metabolism partly through modulating the gut microbial community.